An improved optimization algorithm in cross-layer allocation for multi-user OFDM system - Yaqin PAN; Li ZHANG; Shibing ZHANG (Dianxin kexue)
A cross-layer resource allocation model in multiuser OFDM system was proposed，which combined the channel state in physical layer and the user’s queue in MAC layer.The proposed hybrid optimization algorithm made use of the advantages of genetic algorithm and tabu search algorithm to improve the crossover of genetic algorithm.It would improve the global search ability，converge to the global optimal value faster，solve the cross-layer resource allocation problem more effectively and meet the user’s quality of service better.The simulation results show that the improved hybrid algorithm increases the throughput，reduces the average delay and improves the QoS of the system.